Automatic face reconstruction system - Rahim, Nur Nazihah; Abd Malek, Nur Azrin; Zeki, Akram M.; Abubakar, Adamu (2014)
A face can be sketch by freehand based on the evidence of an eyewitness description which is necessary for the Detectives to tract the looks of the offender. This process is slow; moreover there are some factors which cannot be assumed by the artist, including weight, hair color and length, and eye color. However, if this process is conducted correctly, the result should bear a striking resemblance to the individual. As with composite drawings, an image of the resulting face can then be distributed among law enforcement personnel or to the general public. The reconstructed face should be photographed in such a way that there is no perspective distortion. This paper presents Face Reconstruction for Identification that approach is relatively same with the sketching by freehand. However, this system will reconstruction and generate the face automatically. This will create an effectiveness and efficiency in identifying and recognize the offender.